AS BIBLIOTECAS ESCOLARES DO ENSINO MÉDIO E A FORMAÇÃO DO LEITOR LITERÁRIO: UM ENCONTRO POSSÍVEL? - Fontana, Ana Cláudia Costa (2014)
This study aims to describe the structure of school libraries in high schools in Ponta Grossa –PR, to understand their functioning and the role they have (if any) in promoting reading, mainly of literature. It presents the results of a qualitative investigation with a descriptive approach, developed throughout the year 2013. Data was collected in five State schools in Ponta Grossa – PR and the analysis was carried out based on the reflections of Ezequiel Theodoro da Silva, Luís Milanesi, Rovilson da Silva, Bernadete Campello, Ana Maria Machado, Michele Pètit, Teresa Colomer and others. The places which were called libraries in each institution taking part in the research were investigated, and the people responsible for these spaces, as well as Portuguese teachers and the high school students, provided the researcher with information. In addition to highlighting the libraries profile, some alternatives such as partnerships are proposed for the transformation of the current scenery aiming at its improvement.